MANAJEMEN MUTU PENDIDIKAN TINGGI BIDANG PARIWISATA - Sutono, Anang (2016)
Increasing competition of tourism world is less responded by higher tourism education institutions. Demands of the quality tourism college graduates increased along with the growth of tourism industry. Carrying capacity of tourism development does not expect cheap prices. One of the important thing is the quality of human resources that produced by higher tourism education institutions that have good quality. Policies, standards, and quality management should be a unity in governance in order to produce graduates who are qualified in accordance with the needs of the tourism world.The research objective is to obtain an overview and to analyze policies, standards, and quality management as well as develop a hypothetical model of quality management of tourism education institutions. The approach of this research is qualitative research with case study at Trisakti Institute of Tourism, Jakarta. The analyzing steps use interactive model. The result of this research showed that the quality policies just continue the elder policies, there is not yet new quality policy. Education quality standards arranged by government policies, there is not yet new quality standards that improved after there are new government policies (improvements are still in the process). Education quality planning refers to government policy and identifying problems to focus on the quality of teaching and learning, there is no support by human resources in planning process and improvement internal quality system concept. Organizing the quality of education is the responsibility of the chairman of MR and at operational level especially socialization and quality system documentation is still lacking (there is no unit or quality group of each study program or department). Implementation of quality education focused on teaching and learning, the quality system is still limited of quality implementation to ensure the quality of teaching and learning. The main activities and supporting activities have not yet a quality manual as guidance in the implementation of qualified activities. Education quality control and monitoring restricted on activities that related with teaching and learning (focus on student).Recommendation from this research is the require to optimize the function of the quality culture and transformative leader in optimizing the performance of policies, the establishment of quality standards as a norm and establishing quality management system that produces excellent graduates.; Meningkatnya persaingan dalam dunia pariwisata kurang direspon oleh lembaga pendidikan tinggi pariwisata. Tuntutan terhadap mutu lulusan perguruan tinggi pariwisata semakin meningkat seiring dengan tumbuhnya industri pariwisata. Daya dukung perkembangan pariwisata tidak lagi mengharapkan harga murah. Sumber daya manusia (SDM) berkualitas yang dihasilkan oleh STP bermutu diperlukan guna mendorong daya saing industri pariwisata. Kebijakan, standar, manajemen mutu seharusnya menjadi satu kesatuan dalam tatakelola sekolah tinggi pariwisata guna menghasilkan lulusan yang memiliki kualifikasi sesuai dengan kebutuhan dunia pariwisata.Tujuan penelitian untuk memperoleh gambaran dan menganalisis kebijakan, standar, manajemen mutu dan mengembangkan model manajemen mutu sekolah tinggi pariwisata (STP). Peneliti menggunakan pendekatankualitatif dengan studi kasus pada STP Trisakti Jakarta. Tahapan analisis menggunakan model interaktif. Penelitian menunjukan kebijakan mutu melanjutkan kebijakan lama (incremental), belum ada terobosan kebijakan mutu yang baru. Standar mutu pendidikan disusun berdasarkan kebijakan pemerintah, belum ada standar mutu yang baru hasil perbaikan setelah ada kebijakan baru (masih dalam proses). Perencanaan mutu mengacu pada kebijakan mutu pemerintah dan hasil identifikasi masalah. Fokus masalah mutu pada pengajaran dan pembelajaran, belum ada dukungan SDM dalam merencanakan, memperbaiki konsep sistem mutu internal. Pengorganisasian mutu menjadi tanggung jawab ketua SPMI pada level operasional terutama sosialisasi. Dokumentasi sistem mutu masih kurang dan secara struktur belum ada unit atau gugus mutu pada setiap prodi atau jurusan. Implementasi mutu.Implementasi mutu fokus menjamin kualitas pada pengajaran dan pembelajaran. Kegiatan utama maupun kegiatan pendukung belum memiliki manual mutu sebagai guidance dalam pelaksanaan kegiatan yang bermutu. Pengendalian dan pengawasan mutu terbatas pada kegiatan pengajaran dan pembelajaran (fokus pada mahasiswa). Rekomendasi dalam penelitian yaitu perlunya mengoptimalkan fungsi budaya mutu dan pemimpin yang transformatif untuk mengoptimalkan kinerja kebijakan, penetapan standar mutu sebagai norma serta membangun sistem manajemen mutu yang menghasilkan lulusan bermutu.